An Isolable Terminal Imido Complex of Palladium and Catalytic Implications - Grünwald, Annette; Orth, Nicole; Scheurer, Andreas; Heinemann, Frank Wilhelm; Pöthig, Alexander; Munz, Dominik (Angewandte Chemie International Edition, 2018)
Keywords: C−H activation; palladium nitrene complexes; small-molecule activation; homogeneous catalysis; palladium imido complexes

Aromaticity and sterics control whether a cationic olefin radical is resistant to disproportionation - Messelberger, Julian; Grünwald, Annette; Goodner, Stephen J.; Zeilinger, Florian; Pinter, Piermaria; Miehlich, Matthias; Heinemann, Frank Wilhelm; Hansmann, Max M.; Munz, Dominik (Chemical Science, 2020)
We elucidate why some electron rich-olefins such as tetrathiafulvalene (TTF) or paraquat (1,1 '-dimethyl-4,4 '-bipyridinylidene) form persistent radical cations, whereas others such as the dimer of N,N '-dimethyl benzimidazolin-2-ylidene (benzNHC) do not. Specifically, three heterodimers derived from cyclic (alkyl) (amino) carbenes (CAAC) with N,N '-dimethyl imidazolin-2-ylidene (NHC), N,N '-dimethyl imidazolidin-2-ylidene (saNHC) and N-methyl benzothiazolin-2-ylidene (btNHC) are reported. Whereas the olefin radical cations with the NHC and btNHC are isolable, the NHC compound with a saturated backbone (saNHC) disproportionates instead to the biscation and olefin. Furthermore, the electrochemical properties of the electron-rich olefins derived from the dimerization of the saNHC and btNHC were assessed. Based on the experiments, we propose a general computational method to model the electrochemical potentials and disproportionation equilibrium. This method, which achieves an accuracy of 0.07 V (0.06 V with calibration) in reference to the experimental values, allows for the first time to rationalize and predict the (in)stability of olefin radical cations towards disproportionation. The combined results reveal that the stability of heterodimeric olefin radical cations towards disproportionation is mostly due to aromaticity. In contrast, homodimeric radical cations are in principle isolable, if lacking steric bulk in the 2,2 ' positions of the heterocyclic monomers. Rigid tethers increase accordingly the stability of homodimeric radical cations, whereas the electronic effects of substituents seem much less important for the disproportionation equilibrium.
CRIS-Team WoS Importer:2020-05-26

Bright luminescent lithium and magnesium carbene complexes - Pinter, Piermaria; Schüßlbauer, Christoph; Watt, Fabian A.; Dickmann, Nicole; Herbst-Irmer, Regine; Morgenstern, Bernd; Grünwald, Annette; Ullrich, Tobias; Zimmer, Michael; Hohloch, Stephan; Guldi, Dirk Michael; Munz, Dominik (Chemical Science, 2021)
We report on the convenient synthesis of a CNC pincer ligand composed of carbazole and two mesoionic carbenes, as well as the corresponding lithium- and magnesium complexes. Mono-deprotonation affords a rare "naked" amide anion. In contrast to the proligand and its mono-deprotonated form, tri-deprotonated s-block complexes show bright luminescence, and their photophysical properties were therefore investigated by absorption- and luminescence spectroscopy. They reveal a quantum yield of 16% in solution at ambient temperature. Detailed quantum-chemical calculations assist in rationalizing the emissive properties based on an Intra-Ligand-Charge-Transfer (ILCT) between the carbazolido- and mesoionic carbene ligands. (Earth-)alkali metals prevent the distortion of the ligand following excitation and, thus, by avoiding non-radiative deactivation support bright luminescence.
CRIS-Team WoS Importer:2021-05-07

Carbene derived diradicaloids-building blocks for singlet fission? - Munz, Dominik; Messelberger, Julian; Grünwald, Annette; Pinter, P.; Hansmann, Martin Leo (Chemical Science, 2018)

Carbon Dioxide Activation by a Palladium Terminal Imido Complex - Goodner, Stephen J.; Grünwald, Annette; Heinemann, Frank Wilhelm; Munz, Dominik (Australian Journal of Chemistry, 2019)
We recently reported the first example of a palladium(ii) terminal imido complex. We proposed that this complex features exceptional high nucleophilicity at the nitrogen atom and a peculiar zwitterionic electronic structure with an anti-bonding highest-occupied molecular orbital (HOMO). This complex swiftly activated moderately acidic CH, OH, and NH bonds and also reacted with dihydrogen. However, unambiguous nucleophilic reactivity with substrates not featuring a hydrogen atom could not be observed. Herein, we now show that this nucleophilic complex also reacts with CO2 to give a ring-strained four-membered palladium(ii) carbamate complex. Remarkably, the same product is obtained in the reaction of the related bisamido complex, albeit at a slower reaction rate. Density functional theory calculations indicate that the addition of CO2 does not proceed via initial 1,2-addition across the Pd-N bond, but instead through nucleophilic attack by the imido (amido respectively) nitrogen atom.
CRIS-Team Scopus Importer:2019-09-24

Erratum: Aromaticity and sterics control whether a cationic olefin radical is resistant to disproportionation (Chem. Sci. (2020) 11 (4138-4149) DOI: 10.1039/D0SC00699H) - Messelberger, Julian; Grünwald, Annette; Goodner, Stephen; Zeilinger, Florian; Pinter, Piermaria; Miehlich, Matthias; Heinemann, Frank Wilhelm; Hansmann, Max M.; Munz, Dominik (Chemical Science, 2021)
The authors regret that funding details were incorrect in the acknowledgements section of the original article. The corrected acknowledgements section for this article is shown below.
CRIS-Team Scopus Importer:2021-07-16

How to tame a palladium terminal imido - Munz, Dominik; Grünwald, Annette (Journal of Organometallic Chemistry, 2018)
Keywords: CASSCF; DFT; Carbene; Palladium; Imido; NHC

Oxidative Addition of Water, Alcohols, and Amines in Palladium Catalysis - Grünwald, Annette; Heinemann, Frank Wilhelm; Munz, Dominik (Angewandte Chemie International Edition, 2020)
The homolytic cleavage of O-H and N-H or weak C-H bonds is a key elementary step in redox catalysis, but is thought to be unfeasible for palladium. In stark contrast, reported here is the room temperature and reversible oxidative addition of water, isopropanol, hexafluoroisopropanol, phenol, and aniline to a palladium(0) complex with a cyclic (alkyl)(amino)carbene (CAAC) and a labile pyridino ligand, as is also the case in popular N-heterocyclic carbene (NHC) palladium(II) precatalysts. The oxidative addition of protic solvents or adventitious water switches the chemoselectivity in catalysis with alkynes through activation of the terminal C-H bond. Most salient, the homolytic activation of alcohols and amines allows atom-efficient, additive-free cross-coupling and transfer hydrogenation under mild reaction conditions with usually unreactive, yet desirable reagents, including esters and bis(pinacolato)diboron.
CRIS-Team WoS Importer:2020-10-09

Transmetalation from Magnesium–NHCs—Convenient Synthesis of Chelating π-Acidic NHC Complexes - Messelberger, Julian; Grünwald, Annette; Stegner, Philipp; Senft, Laura; Heinemann, Frank Wilhelm; Munz, Dominik (Inorganics, 2019)
The synthesis of chelating N-heterocyclic carbene (NHC) complexes with considerable -acceptor properties can be a challenging task. This is due to the dimerization of free carbene ligands, the moisture sensitivity of reaction intermediates or reagents, and challenges associated with the workup procedure. Herein, we report a general route using transmetalation from magnesium-NHCs. Notably, this route gives access to transition-metal complexes in quantitative conversion without the formation of byproducts. It therefore produces transition-metal complexes outperforming the conventional routes based on free or lithium-coordinated carbene, silver complexes, or in situ metalation in dimethyl sulfoxide (DMSO). We therefore propose transmetalation from magnesium-NHCs as a convenient and general route to obtain NHC complexes.
CRIS-Team WoS Importer:2019-06-28